Biblical discourses and compulsory monogamy among the Vatsonga people in South Africa - Shingange, Themba (Hervormde teologiese studies, 2024)
The 19th-century missionary-biblical discourses that marked the missionary-colonial project promulgated under the guise of Christianisation and civilisation of the heathens in Africa rendered the recipients as slaves. In Africa, the perpetual legacy of this project still manifests among others by the continued demonisation of African cultural practices. Among the vast South African conventional practices that were frowned upon by the missionaries and continue to be demonised through biblical rhetoric is polygamy. This article investigated how the 19th-century missionaries’ biblical discourses promulgated compulsory monogamy among the Vatsonga people in South Africa. It further looked at how the narrative continues to be spread by Christians using biblical discourses in contemporary South Africa. The article argued that this narrative is tantamount to what Wa Thiong’o calls a ‘cultural bomb’, which uses biblical discourses to eradicate African cultural practices. It further contended that the hegemonic superiority complex of Western epistemologies and cultural practices needs to be problematised. Thus, the article used the desktop research methodology to collect and analyse data. The findings revealed that 19th-century biblical discourses are still used as a colonial tool to disregard the Vatsonga cultural marital practices.Contribution: This article aims to contribute to the body of knowledge and discourses that address the legacies of colonialism around the coming of missionaries in Africa. Therefore, this task was sought to be completed by the decolonial call to change the narrative.